Bibliometric analysis of Asian Pacific Journal of Tropical Medicine from 2008 to 2019 - Taha Hussein Musa; Abdelaziz Adam Idriss Arbab; Hassan Hussein Musa (Intelektual Pustaka Media Utama, 2020)
The purpose of the study is to assess the scientific research productions in Asian Pacific Journal of Tropical Medicine (APJTM) from its first issue up to Dec 2019. We used the Web of Science Core Collection (SCI-EXPANDED, SSCI) to extract the relevant documents. Additionally, the data analysis using ORIGIN PRO 2018, HistCite, bibliometrix R-package, and VOSviewer. Var1.6.6. A total of 2,137 publications of APJTM. A total of 2,136 documents were retrieved, with received 13956 citations, with an average mean 6.63 citations per article, an h-index of 38. The most frequently occurring keywords in this analysis were Malaria, dengue, apoptosis, antioxidant, rate, invasion and anopheles stephesi and inflammation. The study provided the comprehensive and general overview for APJTM journal over its history from the first issue up-to-date. Moreover, the findings provide an insight into the frequency of citations for top-cited articles published in APJTM as well as the quality of the works, journals, trends of publications steering in APJTM.